Adapting or resisting: The resonance of Pancasila's values among Indonesian students in Malaysia - Dermawan, Andy; Al-Giffari, Haekal Adha; Fitria, Vita (Jurnal Civics: Media Kajian Kewarganegaraan, 2024)
Pancasila, the foundational philosophy of Indonesia, serves as a unifying force in a diverse nation characterized by myriad islands, ethnicities, races, and religions. In a world where globalization and migration are prevalent, understanding how national values are maintained by citizens living abroad becomes increasingly significant. This study focuses on Indonesian students at the International Islamic University Malaysia (IIUM), a group representing a microcosm of the Indonesian diaspora. It explores how these students nurture and strengthen their nationalism and internalize Pancasila values despite residing in a foreign country. Utilizing qualitative research methods, with semi-structured interviews as a primary approach to dive deeper into the experiences of these individuals, the study reveals intricate dynamics of cultural adaptation, identity preservation, and the reinforcement of national values. Three thematic insights emerge from the analysis: the role of Pancasila in promoting openness and understanding among diverse groups, the importance of diversity as a reflection of Indonesian society itself, and the complex sense of nationalism experienced by students living abroad. These findings shed light on the dynamic process of internalizing national values within the Indonesian diaspora and contribute to a broader understanding of how cultural identity and cohesion can be maintained across borders. The study highlights the importance of community, cultural practices, and the role of education in fostering a sense of belonging and nationalism among Indonesians abroad, providing valuable insights for policymakers, educators, and diaspora communities striving to preserve national identity in a globalized world.